2014
DOI: 10.1186/1471-2334-14-122
|View full text |Cite
|
Sign up to set email alerts
|

Comparative impact of antiretroviral drugs on markers of inflammation and immune activation during the first two years of effective therapy for HIV-1 infection: an observational study

Abstract: BackgroundFew studies have compared the impact of different antiretroviral regimens on residual immune activation and inflammation with discordant results. Aim of the study was to investigate the impact of various antiretroviral regimens on markers of immune activation and inflammation during the first two years of effective therapy.MethodsWe studied HIV-infected antiretroviral-naïve patients who began cART with either abacavir/lamivudine or tenofovir/emtricitabine, combined with ritonavir-boosted lopinavir (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
42
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 42 publications
8
42
1
Order By: Relevance
“…In addition, co-infection from other viruses, such as cytomegalovirus and Epstein-Barr virus, are a consequence of mucosal immune dysfunction due to decreased CD4 T-cells in the acute phase and the loss of intestinal barriers that may translocate bacteria to systemic circulation. 12 The results from this study align with Maartens et al 11 after initiating ART, the VL levels decreased below the equipment's minimum limit of detection in almost all of the patients during the 3 months of ART. 11 These results support the antigen stimulation theory.…”
Section: A B D Csupporting
confidence: 78%
“…In addition, co-infection from other viruses, such as cytomegalovirus and Epstein-Barr virus, are a consequence of mucosal immune dysfunction due to decreased CD4 T-cells in the acute phase and the loss of intestinal barriers that may translocate bacteria to systemic circulation. 12 The results from this study align with Maartens et al 11 after initiating ART, the VL levels decreased below the equipment's minimum limit of detection in almost all of the patients during the 3 months of ART. 11 These results support the antigen stimulation theory.…”
Section: A B D Csupporting
confidence: 78%
“…The in vivo study showed that treatment with tenofovir-DF/ emtricitabine with atazanavir boosted ritonavir does not significantly affect PAF metabolism according to published data suggesting that this combination decreases inflammatory and coagulation markers [17][18][19]. On the contrary, abacavir/lamivudine with atazanavir boosted ritonavir exhibited a gradual increase in bound and total PAF levels with a pronounced effect at the end of the study.…”
Section: Discussionmentioning
confidence: 82%
“…Some of those have demonstrated that plasma levels of inflammatory markers significantly fell while others have reported no significant change. In most cases, hsCRP remains unchanged or even increases [17,18,25]. Mechanism by which abacavir containing regimens affects inflammatory pathways is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations